Profitability as a Moderator of Intellectual Capital, Social Responsibility, and Enterprise Risk Management Effects on Firm Value - Suharsono, Judi; Wilamsari, Feni; Fithrianto, M Novan; Andrianata, Mufid; Nisak, Choirun (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
The purpose of this research is to investigate the effect of Intellectual Capital (IC), Corporate Social Responsibility (CSR), and Enterprise Risk Management (ERM) on firm value, with profitability as a moderating variable. This study is motivated by the inconsistent findings in previous research regarding the influence of IC, CSR, and ERM on firm value, particularly in emerging markets such as Indonesia. In recent years, the food and beverage sector in Indonesia has experienced dynamic growth, driven by changing consumer behavior, digital transformation, and increasing investor attention. Despite this, many firms in the sector still face challenges in maintaining sustainable value creation. The scope of this investigation includes food and beverage sector firms listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. Explanatory inquiry is employed as the research method, using a population of 72 firms and a sample of 22 firms selected through purposive sampling. The data were analyzed using moderating regression analysis with the help of EViews 13 software. The findings revealed that Intellectual Capital, Corporate Social Responsibility, and Enterprise Risk Management did not significantly influence firm value, and profitability did not moderate these relationships.